O roli retoryki i erystyki w kształceniu kultury politycznej Polaków - Hordecki, Bartosz (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2009)
The relations between rhetoric and politics is ernal and indestructible. Man is a political being while politics is always exercised applying various argumentative and persuasive tools. This fact has been commented upon since the ori human communities. Both rhetoric and eristic can be exercised as disciplines that facilitate the emergence of an understanding and trustful public domain. Nevertheless, rhetoric and eristic can only fon in such a manner provided that other disciplines which make up the current system of education in political science, and education in general, function in a similar way. Neither rhetoric nor eristic will contribute to a public debate which o consensus as long atical and economic system, including schooling, promotes individuls who can compete most skillfully.